The interaction between dietary fiber and gut microbiota, and its effect on pig intestinal health - Hu, Ruiqi; Li, Shuwei; Diao, Hui; Huang, Chongbo; Yan, Jiayou; Wei, Xiaolan; Zhou, Mengjia; He, Peng; Wang, Tianwei; Fu, Hongsen; Zhong, Chengbo; Mao, Chi; et al. (Frontiers in Immunology, 2023)
Intestinal health is closely associated with animal health and performance and consequently influences the production efficiency and profit in feed and animal production systems. The gastrointestinal tract (GIT) is the main site of the nutrient digestive process and the largest immune organ in the host, and the gut microbiota colonizing the GIT play a key role in maintaining intestinal health. Dietary fibre (DF) is a key factor in maintaining normal intestinal function. The biological functioning of DF is mainly achieved by microbial fermentation that occurs mainly in the distal small intestine and large intestine. Short-chain fatty acids (SCFAs), the main class of microbial fermentation metabolites, are the main energy supply for intestinal cells. SCFAs help maintain normal intestinal function, elicit immunomodulatory effects to prevent inflammation and microbial infection and are vital for the maintenance of homeostasis. Moreover, DF is able to alter the gut microbiota composition due to its distinct characteristics. Therefore, understanding the role of DF in modulating gut microbiota and how it influences intestinal health is essential. This review gives an overview of DF and its microbial fermentation process and investigates the effect of DF on the alteration of gut microbiota composition in pigs. The interactive effects between DF and gut microbiota, particularly associated with SCFA production, on intestinal health are illustrated as well.